Cecal volvulus following laparoscopic cholecystectomy: A case report and literature review - Mahdi Aljamal; Bashar Jaber; Ali Shakhshir (Radiology Case Reports)
Laparoscopic cholecystectomy has become the gold standard for the treatment of symptomatic gallbladder stones. Minimally invasive operations are currently preferred by surgeons and patients. Intestinal volvulus after laparoscopic cholecystectomy has been reported before, but it is still a rare complication of laparoscopic procedures, i.e., including laparoscopic cholecystectomy. To date, few cases were found specifically mentioning cecal volvulus after laparoscopic cholecystectomy; other articles had mentioned other intestinal volvulus after other laparoscopic procedures. We are reporting a case of cecal volvulus that developed in a 43-year-old woman 2 days after laparoscopic cholecystectomy, which was treated successfully with exploratory laparotomy with limited right hemicolectomy and ileocolic primary anastomosis. More studies have to be made to determine the incidence and causative relation between laparoscopic surgeries and volvulus, and volvulus should be considered in every patient who complains of postoperative abdominal pain and symptoms of intestinal obstruction.